2014
DOI: 10.1002/cmdc.201400042
|View full text |Cite
|
Sign up to set email alerts
|

1‐(1H‐Indol‐3‐yl)ethanamine Derivatives as Potent Staphylococcus aureus NorA Efflux Pump Inhibitors

Abstract: The synthesis of 37 1-(1H-indol-3-yl)ethanamine derivatives, including 12 new compounds, was achieved through a series of simple and efficient chemical modifications. These indole derivatives displayed modest or no intrinsic anti-staphylococcal activity. By contrast, several of the compounds restored, in a concentration-dependent manner, the antibacterial activity of ciprofloxacin against Staphylococcus aureus strains that were resistant to fluoroquinolones due to overexpression of the NorA efflux pump. Struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 67 publications
(59 reference statements)
1
25
0
Order By: Relevance
“…183 Among the prepared indole derivatives, compound 17 ( Figure 5) displayed the most promising NorA inhibitory activity with an MPC 4 of 1 µM for ciprofloxacin against SA1199B. 184 In addition, even more potent bis-indole compounds were disclosed in the patent application with compound 5 (Figure 1) as a representative example, which showed an MPC 4 below 0.4 µM for ciprofloxacin against SA1199B. Cytotoxicity assays against three different human cell lines were performed and 5 was considered as noncytotoxic at a concentration of 1 µM.…”
Section: Aryl Alkenyl Amidesmentioning
confidence: 99%
See 3 more Smart Citations
“…183 Among the prepared indole derivatives, compound 17 ( Figure 5) displayed the most promising NorA inhibitory activity with an MPC 4 of 1 µM for ciprofloxacin against SA1199B. 184 In addition, even more potent bis-indole compounds were disclosed in the patent application with compound 5 (Figure 1) as a representative example, which showed an MPC 4 below 0.4 µM for ciprofloxacin against SA1199B. Cytotoxicity assays against three different human cell lines were performed and 5 was considered as noncytotoxic at a concentration of 1 µM.…”
Section: Aryl Alkenyl Amidesmentioning
confidence: 99%
“…Furthermore, another research group was investigating indole nucleus as a promising scaffold for the synthesis of novel antimicrobial agents . Among the prepared indole derivatives, compound 17 (Figure ) displayed the most promising NorA inhibitory activity with an MPC 4 of 1 µM for ciprofloxacin against SA1199B . In addition, even more potent bis ‐indole compounds were disclosed in the patent application with compound 5 (Figure ) as a representative example, which showed an MPC 4 below 0.4 µM for ciprofloxacin against SA1199B.…”
Section: Efflux Pump Inhibitors Of Selected Clinically Relevant Pathomentioning
confidence: 99%
See 2 more Smart Citations
“…10 Tertbutyl (2-(3-hydroxyureido)-2-(1H-indol-3-yl)ethyl) carbamate, which is not toxic to human cells, was also found to be an active indolic NorA inhibitor. 11 Azole-containing compounds such as fluconazole, ketoconazole, and itraconazole are the most widely used antifungal agents in the clinic. 12,13 Despite all the claims, many studies have demonstrated the ineffectiveness of fluconazole against Candida krusei, 14,15 which has been recognized as a potentially multidrug-resistant fungal pathogen.…”
Section: Introductionmentioning
confidence: 99%